Penting Adanya Hubungan Sekolah dan Masyarakat dalam Pendidikan di Sekolah Dasar - Nur Hana; Auliya Sakinah; Fadilla Tussyah Raini; Syahrial Syahrial (Journal on Education, 2024)
The school's relationship with the community aims to advance the quality of children's learning and growth. A school is a building or institution for learning and teaching as well as a place to receive and give lessons. Meanwhile, society in simple terms is a group of people who interact or associate with each other with the same interests. School and society are two environments that cannot be separated, both have a very close relationship. School-community relations are a communication process between the school and the community to increase the need for educational activities and encourage community interest and cooperation in improving and developing the school. The community is expected to support and participate in developing the educational process in elementary schools. In this case, management needs to involve the community in educational activities in elementary schools.